Infant communication. How should we define this, and is it important?. Issue 6 (December 2022) - Harding, Celia; Whiting, Lisa; Petty, Julia; Edney, Sarah; Murphy, Rebecca; Crossley, Siew-Lian
Abstract: Infants born preterm are at high risk of developing speech, language and communication difficulties in their early years. Published literature investigating early parent - infant interaction often describe "communication" with reference to early bonding. Strategies such as bonding, attachment, responsiveness to cues and skin to skin care are essential precursor skills for the development of productive dyadic relationships. However, studies that consider speech, language and communication support for families when receiving care for their infant on a neonatal unit are sparse. This paper discusses communication from a linguistic perspective and the authors argue why this is important.